The Impact of Sequence of Chemotherapy and EGFR-TKI Treatment on Different EGFR Mutation Lung Adenocarcinoma. (2nd November 2015) - Chung, Fu-Tsai; Ho, Ming-Yun; Fang, Yueh-Fu; Hshieh, Meng-Heng; Wang, Tsai-Yu; Kuo, Chih-Hsi; Chen, Hao-Cheng; Wang, Chun-Hwa; Lin, Shu-Min; Yu, Chih-Teng; Lin, Horng-Chyuan; Kuo, Han-Pin
Abstract : Objectives . Chemotherapy as first-/second-line treatment in different epidermal growth factor receptor ( EGFR ) mutation lung adenocarcinoma remains controversial. Methods . Consecutive patients were collected between 2009 and 2012. Patients were divided into two groups (1st-line chemotherapy: n = 56 and 2nd-line chemotherapy: n = 55). Their outcomes profiles were analyzed. Results . The overall survival (OS) of all patients (390 versus 662 days, p < 0.0001), as well as both progression-free survival (PFS, 151 versus 252 days, p = 0.0001) and OS (308 versus 704 days, p = 0.0001) of patients with L858R mutation ( n = 63), who received 2nd-line chemotherapy, was significantly poor. By univariate and multivariate analysis, 2nd-line chemotherapy, and L858R mutation were significantly related to poor PFS and OS. Conclusion . In advanced lung adenocarcinoma, L858R mutation and 2nd-line chemotherapy caused a poor outcome. It is a consideration to choice of 1st-line chemotherapy in these subjects. A prospective design is warranted to confirm this finding.